Financial dollarization in Russia: causes and consequences - Alexey Ponomarenko; Alexandra Solovyeva; Elena Vasilieva (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
We review some aspects of financial dollarization in Russia, applying the main relevant theories to analyze the dynamics of several dollarization indicators. An econometric model of the short run dynamics of deposit and loan dollarization is estimated for the last decade. We find that ruble appreciation was the main driver of the de-dollarization that occurred then and of the later episode of renewed dollarization. We estimate the overall (and sector-al) currency mismatches of the Russian economy. The results show a gradual improvement of the net foreign currency position of the public sector, where we have seen significant accumulation of international reserves by the Bank of Russia and repayment of government debt. Evidence is also presented for the significant currency risk vulnerability of the nonbanking private sector. Several existing empirical studies are examined in order to assess the growth losses of the Russian economy following the crisis of 2008, which was linked with the financial dollarization.
URN:NBN:fi:bof-201408072045
Keywords: E44; F34; G32; 330; Financial dollarization; currency mismatch; balance sheet effects; Russia